Atomistic understanding of the subsurface damage mechanism of silicon (100) during the secondary nano-scratching processing. (15th June 2022) - Yuan, Song; Guo, Xiaoguang; Liu, Shengtong; Li, Penghui; Liu, Fumin; Zhang, Lemin; Kang, Renke
Abstract: Ultra-precision grinding is a fundamental machining method as for silicon. In grinding, abrasive particles repetitively scratch on the workpiece surface, and the subsurface damage caused by the initial scratching exerts a remarkable effect on the subsequent processing. Nonetheless, the previous researches regarding the subsurface damage mechanism of silicon ignore the influence caused by the initial scratching. Herein, a damage model was constructed via the initial scratching method, and the influence mechanism of the secondary nano-scratching on the subsurface damage of silicon substrate under different scratching parameters was explored utilizing molecular dynamics simulation. The simulation results show that the dominating removal part under secondary scratching is the amorphous layer induced by the initial scratching, and the secondary scratching without feed can effectively remove prefabrication subsurface damage. The larger scratching depth and tool radius could lead to the increasement of scratching force and scratching temperature so as to increase the thickness of subsurface damage layer. Moreover, the high pressure generated by the collision between the abrasive particles and the substrate will induce the amorphous phase transformation. This study provides a new insight into the mechanism and evolution of subsurface damage during grinding process of silicon from an atomic perspective.